DIMENSI-DIMENSI KUALITAS LAYANAN: PENGUJIAN MODEL KUALITAS LAYANAN DARI PERSPEKTIF EUROPA - Chandra Kuswoyo; Rully Arlan Tjahyadi (Universitas Kristen Maranatha, 2017)
The purpose of this paper was to examine the role of functional quality, technical quality, and corporate image on customer satisfaction. Individual-level analyses from a sample of 265 students of Management study at Economic Faculty of Maranatha Christian University indicate that functional quality and corporate image are positively and significantly associated with customer satisfaction. Research findings indicate that functional quality and corporate image were found to be more important than technical quality in determining customer attitude.Â Keywords: Functional Quality, Technical Quality, Corporate Image, Customer Satisfaction